2005
DOI: 10.1111/j.1444-2906.2005.01097.x
|View full text |Cite
|
Sign up to set email alerts
|

Genes expressed in Japanese flounder Paralichthys olivaceus spleen: analysis of genes involved in immune function

Abstract: Expressed sequence tag (EST) analysis is an efficient tool for gene discovery and for profiling gene expression. A cDNA library developed from messenger RNA of the Japanese flounder, Paralichthys olivaceus spleen was constructed by directional cloning, in order to isolate functional genes involved in immunity in fish. A total of 1010 ESTs from the library were sequenced and compared with sequences in the GenBank database. Of the 1010 ESTs, 618 ESTs (61%) were identified as being homologous with known genes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Based on the quadratic regression analysis for PWG (Y PWG ¼ À0.0378 x 2 þ 3.3064x þ 158.96, R 2 ¼ 0.861), the dietary lipids requirement of young grass carp is estimated to be 43.7 g/kg diet. Fish growth is often related to disease resistance, which has been correlated with immune organ function [4]. Hence, we next investigated the effects of lipids on the head kidney and spleen immune function in young grass carp.…”
Section: Low or Excess Levels Of Dietary Lipids Reduce Growth Performmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the quadratic regression analysis for PWG (Y PWG ¼ À0.0378 x 2 þ 3.3064x þ 158.96, R 2 ¼ 0.861), the dietary lipids requirement of young grass carp is estimated to be 43.7 g/kg diet. Fish growth is often related to disease resistance, which has been correlated with immune organ function [4]. Hence, we next investigated the effects of lipids on the head kidney and spleen immune function in young grass carp.…”
Section: Low or Excess Levels Of Dietary Lipids Reduce Growth Performmentioning
confidence: 99%
“…It has been reported that the head kidney and spleen are the major sites of antibacterial compounds production to protect fish from pathogens in teleosts, which include lysozyme (LA), acid phosphatase, complement and antimicrobial peptides [4,75,76]. In the present study, compared to the optimal dietary lipids supplement, low or excess levels of lipids decrease LA and ACP activities and C3, C4 and IgM contents and down-regulate LEAP-2a, LEAP-2b, Hepcidin and b-defensin-1 mRNA levels in the head kidney and spleen of young grass carp, indicating that low or excess levels of lipids could reduce the immune function in the head kidney and spleen of fish.…”
Section: Low or Excess Levels Of Lipids Reduce The Head Kidney And Spmentioning
confidence: 99%
See 2 more Smart Citations
“…Fish disease resistance is linked to the immune response, which partly relies on the proper function and structure of immune organs, such as the head kidney and spleen, two important lymphatic immune organs (Arma et al, 2005;Seker et al, 2011). In this…”
Section: Introductionmentioning
confidence: 98%